Research on the development strategy of Neijiang Zigong sports city under the background of the construction of the double city economic circle in Chengdu-Chongqing area - Deng Xiaomei (International Journal of Education and Humanities, 2024)
The proposal of the " Outline of the Construction Plan for the Two-city Economic Circle in Chengdu-Chongqing Area " has brought new opportunities for the coordinated development of the sports industry in Neijiang and Zigong. This paper uses the methods of literature, expert interview and induction to analyze the realistic basis, main dilemma and realization path of the development of sports integration in Zigong, Neijiang. The study found that the development of Zigong sports integration in Neijiang is faced with the imperfection of school sports infrastructure resources ; competitive athletes have less mutual cooperation and are not closely linked ; lack of motivation in mass sports events ; there is a lack of characteristics and innovation in the sports industry brand. Therefore, this paper suggests that the two municipal governments take the lead in collaborating with each other and integrating various resources ; optimize regional layout and give full play to complementary advantages and dislocation development ; jointly cultivate outstanding athletes and jointly organize sports events to strengthen exchanges and contacts between the two cities ; lead the high-quality and coordinated development of green sports industry, enhance the initiative of sports development in the two regions, and jointly promote the development of sports integration in Neijiang Zigong